Self-regulated learning strategies, concept understanding and performance in statics - Habibah @ Norehan Haron, 1967-; Awaluddin Mohamed Shaharoun, supervisor; Marlia Puteh; Sekolah Pengajian Siswazah (2012)
Thesis (Ph.D (Pendidikan Kejuruteraan)) - Universiti Teknologi Malaysia, 2012